The National HIgher Education Strategic Plan 2 : Malaysia's global reach : a new dimension - Abdullah, Nur Anisah; Abdul Rahman, Shukran (Ministry of Higher Education Malaysia, 2011)
Phase II of the National Higher Education Strategic Plan to continue tis agenda to strengthen its foundation and effectively strategize to ensure the successful implementation of planned agenda.